Syntheses of CF2H-containing spirocyclopropyloxindoles from in situ generated CF2HCHN2 and 3-ylideneoxindoles. Issue 39 (28th September 2017) - Han, Wen-Yong; Zhao, Jia; Wang, Jian-Shu; Cui, Bao-Dong; Wan, Nan-Wei; Chen, Yong-Zheng
Abstract: A facile and practical [3+2] cycloaddition/ring contraction for the construction of structurally diverse CF2 H-containing spirocyclopropyloxindoles was developed. Starting from isatin-derived 3-ylideneoxindoles and in situ generated CF2 HCHN2, the desired products were obtained in good to excellent results (up to 99% yield and >99:1 trans/cis ) in the absence of metal catalyst. The potential application of the protocol was also demonstrated by the synthesis of the CF2 H-substituted analog of HIV-1 NNRTI inhibitor. Graphical abstract: